KELEMBABAN UDARA DENGAN ALAT HUMYDIMETER PADA LAHAN SAWAH DI KELURAHAN TANAH MERAH - Furqaan Hamsyani; Herijanto Thamrin; Nurul Asiyah (Politeknik Pertanian Negeri Samarinda, 2021)
Humidity is the concentration of water vapor in the air. In agriculture, air humidity is associated with increased productivity and development of cultivated plants, humidity in the environment where it grows can determine the selection of appropriate plant species, the purpose of this study was to determine air humidity in paddy fields between April, May , and June, changes in air humidity at any time describe the water vapor content in the air can be expressed as absolute humidity, relative or vapor pressure deficit, relative humidity compares the actual water vapor content/pressure with its saturation state or the air's capacity to accommodate water vapor. The relationship between air humidity in paddy fields in Tanah Merah Village is relatively low, this is the impact of changes in temperature, quantity and quality of radiation, wind movement, air pressure, vegetation, and availability of water and productivity of irrigated ricefields